Adult foreign body impaction: 11 years of experience in a tertiary center. - Kyling Duvauchelle, Alberto; Barrientos Riveros, Camila; Hunt Pavesi, Karen (Revista Confluencia, 2022)
Background/aims: Impaction of an esophageal foreign body is a medical emergency. Its incidence in recent years has increased. Symptoms include dysphagia, aphagia, chest pain, among others. The treatment of choice is endoscopic extraction. Complications such as perforations, erosions or fistulas have been described. The aim of this study is to characterize the clinic and endoscopic profile of adult patients who consult for this pathology in a tertiary center. Methods: Case series of patients aged over 15 years between 2008-2019 attended in the emergency room of Clínica Alemana de Santiago with suspected or confirmed esophageal foreign body impaction. Electronic clinical records, endoscopic reports and biopsies were reviewed. A descriptive analysis of the data was performed. Results: A total of 324 cases were analyzed. 60,5% of the cases underwent urgent upper gastrointestinal endoscopy. The most frequently reported symptoms were foreign body sensation (67,9%) and hypersalivation (35,4%). The most frequent type of foreign body found was red meat (36,7%). A significantly higher incidence of esophageal foreign body was observed on weekends. Eosinophilic esophagitis was suspected in 37%, there were no cases of malignancy. Complications were rare in our series (0,2%). Conclusion: Eosinophilic esophagitis was the most frequent underlying condition in this series. The results may account for some cultural aspects in the population of the study. Emergency endoscopic therapy is safe and effective. Limitations of this study include the retrospective character. A prospective study to propose a protocol should be developed.
Keywords: Steakhouse syndrome; Eosinophilic esophagitis; Gastrointestinal symptoms